Molecular epidemiology of isolates with multiple mcr plasmids from a pig farm in Great Britain: the effects of colistin withdrawal in the short and long term. (14th August 2018) - Duggett, Nicholas A; Randall, Luke P; Horton, Robert A; Lemma, Fabrizio; Kirchner, Miranda; Nunez-Garcia, Javier; Brena, Camilla; Williamson, Susanna M; Teale, Christopher; Anjum, Muna F
Abstract: Background: The environment, including farms, might act as a reservoir for mobile colistin resistance ( mcr ) genes, which has led to calls for reduction of usage in livestock of colistin, an antibiotic of last resort for humans. Objectives: To establish the molecular epidemiology of mcr Enterobacteriaceae from faeces of two cohorts of pigs, where one group had initially been treated with colistin and the other not, over a 5 month period following stoppage of colistin usage on a farm in Great Britain; faecal samples were also taken at ∼20 months. Methods: mcr-1 Enterobacteriaceae were isolated from positive faeces and was WGS performed; conjugation was performed on selected Escherichia coli and colistin MICs were determined. Results: E. coli of diverse ST harbouring mcr-1 and multiple resistance genes were isolated over 5 months from both cohorts. Two STs, from treated cohorts, contained both mcr-1 and mcr-3 plasmids, with some isolates also harbouring multiple copies of mcr-1 on different plasmids. The mcr-1 plasmids grouped into four Inc types (X4, pO111, I2 and HI2), with mcr-3 found in IncP. Multiple copies of mcr plasmids did not have a noticeable effect on colistin MIC, but they could be transferred simultaneously to a Salmonella host in vitro . Neither mcr-1 nor mcr-3 was detected in samples collected ∼20 months after colistin cessation. Conclusions: We report for the first known time on the presence in Great Britain of mcr-3 from MDR Enterobacteriaceae, which might concurrently harbour multiple copies of mcr - 1 on different plasmids. However, control measures, including stoppage of colistin, can successfully mitigate long-term on-farm persistence.